Combined effects of cadmium exposure and temperature on the annual killifish (Nothobranchius furzeri). (16th July 2018) - Philippe, Charlotte; Hautekiet, Pauline; Grégoir, Arnout F.; Thoré, Eli S.J.; Pinceel, Tom; Stoks, Robby; Brendonck, Luc; Boeck, Gudrun De
Abstract: Freshwater organisms are increasingly exposed to combinations of stressors. However, because it is time‐consuming and costly, research on the interaction of stressors, such as compound toxicity and global warming on vertebrates, is scarce. Studies on multigenerational effects of these combined stressors are almost nonexistent. In the present study, we tested the combined effects of 4 °C warming and cadmium (Cd) exposure on life‐history traits, biomarkers, bioaccumulation, and multigenerational tolerance in the turquoise killifish, Nothobranchius furzeri . The extremely short life cycle of this vertebrate model allows for assessment of sublethal and multigenerational effects within 4 mo. The applied Cd concentrations had only limited effects on the measured endpoints, which suggests that N. furzeri is more resistant to Cd than fathead minnow and rainbow trout. In contrast, the temperature increase of 4 °C was stressful: it delayed female maturation and lowered adult mass and fecundity. Finally, indications of synergistic effects were found on peak fecundity and embryonic survival. Overall, these results indicate the importance of studying chronic and multigenerational effects of combined stressors. Environ Toxicol Chem 2018;37:2361–2371. © 2018 SETAC.